(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aimed to examine the effectiveness of the peer teaching strategy in developing oral reading skills among ninth-grade students in basic education. The study adopted a quasi-experimental design and was conducted on a sample of (36) students selected purposively from two schools in South Al-Sharqiyah Governorate, Oman. The participants were divided into an experimental group and a control group. The research instruments included an observation checklist consisting of (11) skills to measure reading accuracy and fluency, as well as an oral reading test to assess reading comprehension. The instruments were administered before and after the intervention, which lasted four weeks. Statistical analysis using means, standard deviations, and t-tests revealed no statistically significant differences between the two groups in the pre-test. However, statistically significant differences were found in the post-test in favor of the experimental group. The findings indicate that the peer teaching strategy is effective in improving students’ oral reading skills, particularly reading accuracy and comprehension. The study recommends integrating peer teaching strategies into Arabic language instruction and emphasizing oral reading skills across different educational stages.